The challenges of research on documentary information in contemporary world: between armed conflicts and technological advances (Ágora de Heterodoxias, 2024)
We are living in an era of constant volatility, uncertainty, complexity, and ambiguity, commonly referred to as VUCA, an acronym in English proposed by Heifetz et al. (2009). This concept has been widely adopted to refer to the economy, politics, and social studies to address the challenges faced by different organizations, whether they are economic, political, or social in nature. Among the recent challenges, we highlight the outbreak of COVID-19, triggering a global pandemic in 2020, whose effects extend until 2024, and two recent wars: the Russia-Ukraine war since February 2022 and the conflict in the Gaza Strip between the Hamas group and Israel since October 2023. On the other hand, it can be pointed out that VUCA is also linked to the exponential advancement of artificial intelligence (AI) technology, which is unprecedentedly impacting politics, economy, culture, education, research, and people's lifestyles.
Keywords: challenges of research; documentary information; armed conflicts; technological advances